Unusual solutions for catheter placement in haemodialysis patients - Caeiro,Fernando (2013)
Background:Although vascular access is essential for adequate haemodialysis delivery, the systematic use of a patient's venous patrimony may eventually lead to exhaustion of suitable sites for placement of a new vascular access. Case Report: We present two cases of such patients. In the first one we inserted a 55cm catheter through the left external iliac vein, and a 40cm translumbar catheter was placed in the second one. Both interventions were performed percutaneously under radiological guidance. Both patients were anticoagulated after the procedure. Conclusion: Unusual sites for haemodialysis catheter placement may be life saving in selected situations and offer safe and viable alternatives for adequate haemodialysis delivery.